Concurrent compression and meaningful encryption of images using chaotic compressive sensing - Ashwini, K.; Sutha, S.; S., Sountharrajan; Bavirisetti, Durga Prasad (Frontiers in Computer Science, 2024)
The presented research introduces a new approach to simultaneously compressing and encrypting images using chaotic compressive sensing. This technique involves transforming the image into sparser data using the discrete cosine transform basis, which is then compressed through projection onto a lower dimensional space using a measurement matrix designed based on a new chaotic map. The proposed chaotic map produced a Lyapunov exponent value of 2.675 proving its chaotic behavior. The proposed map is also highly sensitive to initial values, making it a secure basis for encryption. The compressed data with the proposed map is then embedded onto a colorful image for transmission. This approach achieves both compression and visually meaningful encryption of images. Quantitative and Qualitative results on the proposed compression-encryption algorithm shows the effectiveness of the methodology against chosen plaintext attacks and cipher-only attacks.